ANALISIS FINANCIAL TECHNOLOGY, INKLUSI KEUANGAN, LITERASI KEUANGAN DAN PENDAPATAN TERHADAP PELAKU UMKM JAKARTA TIMUR - Agnes Claudia Gunawan, (2022)
The purpose of this research is to investigate the influence of financial technology, financial inclusion, financial literacy, and income on the financial behavior of small and medium-sized enterprises (SMEs) in East Jakarta. The population of this study is East Jakarta's SME actors. Non-probability sampling was utilized to choose the sample in this research, and 100 respondents were gathered. The data analysis procedure uses the SmartPLS 3.0 tool to test the hypothesis at a 5% level of significance. The results show that, (1) Financial technology has a negative and insignificant effect on financial behavior, (2) Financial inclusion has a negative and insignificant effect on financial behavior, (3) Financial literacy has a positive and significant effect on financial behavior, (4) Income has a negative and insignificant effect on financial behavior.